2010
DOI: 10.1210/er.2009-0038
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models in Diabetes and Pregnancy

Abstract: The worldwide increase in the incidence of diabetes, the increase in type 2 diabetes in women at reproductive ages, and the cross-generation of the intrauterine programming of type 2 diabetes are the bases for the growing interest in the use of experimental diabetic models in order to gain insight into the mechanisms of induction of developmental alterations in maternal diabetes. In this scenario, experimental models that present the most common features of diabetes in pregnancy are highly required. Several im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
110
0
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(126 citation statements)
references
References 255 publications
(134 reference statements)
6
110
0
10
Order By: Relevance
“…Impairment of the oxidative and nitrosative stress balance can deregulate multiple signaling pathways and cause massive cell damage, apoptotic events, and defective embryonic and fetal development (Sivan et al 1997;Reece et al 2005;Morgan et al 2008;Sugimura et al 2009). In addition, the malformation rate is clearly correlated with increased glucose concentrations (Jawerbaum and White 2010). Experimental results support the notion of hyperglycemia as a teratogen, since high glucose levels (Dienelt and Zur Nieden 2011) or maternal diabetes in vivo as well as exposure to high glucose concentration cause embryonic maldevelopment.…”
Section: Discussionsupporting
confidence: 65%
“…Impairment of the oxidative and nitrosative stress balance can deregulate multiple signaling pathways and cause massive cell damage, apoptotic events, and defective embryonic and fetal development (Sivan et al 1997;Reece et al 2005;Morgan et al 2008;Sugimura et al 2009). In addition, the malformation rate is clearly correlated with increased glucose concentrations (Jawerbaum and White 2010). Experimental results support the notion of hyperglycemia as a teratogen, since high glucose levels (Dienelt and Zur Nieden 2011) or maternal diabetes in vivo as well as exposure to high glucose concentration cause embryonic maldevelopment.…”
Section: Discussionsupporting
confidence: 65%
“…It should be noted that this happened despite a return to normal fetal growth and pancreas weight, clearly illustrating a lack of association between fetal weight and development of BCM (and further risk of type 2 diabetes). Our findings in the oGK/pW fetus do not necessarily contradict the evidence for an adverse influence of maternal diabetes on beta cell formation, as reported in the majority of experimental studies with maternal diabetes induced (not spontaneous) in various models [24]. Beta cell development, differentiation and survival are indisputably controlled by genes.…”
Section: Discussionsupporting
confidence: 82%
“…Consequently, in the present study a preliminary dose response effect of STZ on blood glucose (standardization) was carried out to determine the optimum dose needed to produce stable hyperglycemia in Sprague Dawley rats, as data in the literature could not be relied upon due to broad variability [10,11] . The results indicated that a single intra-peritoneal injection of 40-45, 50-55 and 60-65 mg/kg body weight of STZ could induce hyperglycemia in SD rats after 6 d, but of varying intensities.…”
Section: Discussionmentioning
confidence: 99%